BIODIVERSITAS MAKROALGA DI KAWASAN KONSERVASI GILI MATRA - Rahmi, Disa Aulia; Jefri, Edwin; Buhari, Nurliah; Hotmariyah, Hotmariyah (Universitas Mataram, 2025)
Macroalgae are a group of lower marine plants commonly referred to as thalloid plants. The diversity of macroalgae in tropical regions, particularly in eastern Indonesia, is very high due to the area being part of the Wallacea region. This study aims to determine the level of diversity and distribution of macroalgae in these waters. The method used is the line transect method, with data analysis including ecological indices and distribution patterns. The results show that the diversity index ranges from 2.45 to 2.80, which falls into the medium category. The evenness index ranges from 0.80 to 0.81, classified as high, while the dominance index ranges from 0.09 to 0.11, which is considered low. The distribution pattern of macroalgae at stations 1, 2, and 3 ranges from 1.37 to 1.49, indicating a clustered distribution pattern. This suggests that the environmental conditions in the waters of Gili Air are stable and conducive to the growth of macroalgae, with no species dominating the ecosystem.